2021
DOI: 10.1002/jctb.6868
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals bioremediation and water softening using ureolytic strains Metschnikowia pulcherrima and Raoultella planticola

Abstract: BACKGROUND: The recalcitrant nature of lead (Pb) and mercury (Hg) to degradation represents a real risk to living creatures and their surrounding ecosystems. Therefore, this study employed ureolytic fungal strain Metschnikowia pulcherrima (29A) and bacterial strain Raoultella planticola (VIP) in their removal using the promising CaCO 3 bioprecipitation technique, for the first time.RESULTS: Out of 50 isolates, strains 29A and VIP were selected based on their highest ureolytic activity, followed by minimum inhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Despite they were screened from different environmental habitats with different contamination content. Some of them exhibited characteristic bioremediation capabilities [ 16 ]. The diversity of their phylogeny, namely Basidiomycota, Proteobacteria , and Firmicutes , revealing their metabolic performance to utilize and detoxify xenobiotic compounds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite they were screened from different environmental habitats with different contamination content. Some of them exhibited characteristic bioremediation capabilities [ 16 ]. The diversity of their phylogeny, namely Basidiomycota, Proteobacteria , and Firmicutes , revealing their metabolic performance to utilize and detoxify xenobiotic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is a time consuming, laborious practice and cost-effective. Recently, DOS has been utilized in media engineering to procure the optimal operating conditions for several purposes such as heavy metal removal [ 16 ], enzyme production [ 75 ] protein-drug production [ 74 ] and dye biosorption [ 63 ]. Initially PBD was utilized to screen the most significant factors, based on p-value, which were MB concentration, pH, molasses concentration, inoculum size and NaNO 3 concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was reported that R. planticola (R3) can grow at 1500 ppm lead and was reported that it can remove several heavy metals like lead, manganese, cadmium, copper, zinc and nickel (Bowman et al 2018 ). Raoultella planticola (VIP) was determined the minimum inhibition concentration reached to 350 ppm and completely removed lead at 90 h (Eltarahony et al 2021 ) while the MIC for R. planticola FACU 3 was to 2800 ppm. In this study, TEM was used to investigate the morphological Pb response of two bacterial strains, the highest strain ( R. planticola FACU 3) and lowest strains ( S. xylosus FACU) in cell viability, efficiency of biosorption and Pb uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Raoultella planticola , a ureolytic bacterial strain, transformed Pb 2+ into light grey cerussite (PbCO 3 ), whereas Metschnikowia pulcherrima , a ureolytic fungal strain, transformed Pb 2+ into CaPbO 3 . Such instances were also disclosed by Hg 2+ remediation ( Eltarahony et al, 2021 ). Supplementary Table S1 also lists the final products of different representative HMs formed in MICP.…”
Section: Key Factors Influencing the Performance Of Micp Bioremediationmentioning
confidence: 92%